Manajemen Keunggulan Pelayanan Dalam Membangun Identitas Kompetitif Sekolah Islam Pada Masyarakat Multi Religius - Asshiddiqie, Syaifulloh; Purnomo, Joko (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study employed a qualitative approach using a multi-case study design to explore in depth how service excellence and competitive identity strategies are implemented across several Islamic schools operating within multi-faith communities. The multi-case study design was purposively selected because the focus of this research lies in examining bounded systems in the form of educational institutions with distinctive managerial characteristics, rather than investigating the lived psychological experiences of individuals, which is the primary concern of phenomenological research. Through this approach, the researchers were able to conduct cross-case analysis to compare cases, identify patterns of replication, and generate stronger theoretical abstractions regarding the differentiation of school reputation management strategies in heterogeneous societies. Data were collected through in-depth interviews, observations, and document analysis of school standard operating procedures. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing through source triangulation. The findings reveal that successful Islamic schools have effectively transformed the Islamic value of Ihsan into a standard of professional service, developed an inclusive identity that transcends sectarian boundaries, and fostered parental loyalty based on academic quality and universal ethical values rather than solely on religious sentiment. These findings underscore that the integration of managerial professionalism and spiritual values constitutes a critical factor enabling faith-based educational institutions to achieve social legitimacy and long-term sustainability within diverse and heterogeneous communities.